Military Duties and an Assassination Plot: The Extra Dimension Found in Ancient Egyptian Letters - Thorpe, Susan.
While current and previous research has provided considerable information regarding ancient Egyptian military campaigns, equipment, rank, and custom, this has come primarily from reliefs, inscriptions and military scribal documents. The personal touch found in private correspondence gives an extra dimension to these visual representations and official documents. This added aspect is evidenced in the following selection of letters from the Ramesside and Late Ramesside periods. Those from the Ramesside timeframe provide first-hand information about the responsibilities of a soldier’s life in society when not involved in active service. They give insight into these duties and into the actual people involved, together with their personalities and issues. Still in a military context are four pieces of correspondence from a high-ranking general, dated to the Late Ramesside period. The first is concerned with care for the wounded. The other three are regarding an assassination plot involving the killing of two policemen and the means by which his recipients are to carry this out. This study, by its analysis and discussion of these pieces of personal correspondence, will illustrate the extra dimension such letters can provide–their importance as primary sources of societal and historical information that would otherwise remain unknown.   doi: http://dx.doi.org/10.5913/jarce.54.2018.a014